2013
DOI: 10.1088/0029-5515/53/10/104024
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal options for materials research to advance the basis for fusion energy in the ITER era

Abstract: Well-coordinated international fusion materials research on multiple fundamental feasibility issues can serve an important role during the next ten years. Due to differences in national timelines and fusion device concepts, a parallel-track (multimodal) approach is currently being used for developing fusion energy. An overview is given of the current state-of-the-art of major candidate materials systems for next-step fusion reactors, including a summary of existing knowledge regarding operating temperature and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(39 citation statements)
references
References 117 publications
0
39
0
Order By: Relevance
“…These steels are expected to exhibit low-temperature embrittlement problems, but, on the positive side, their high density of nano-scale precipitates and microstructures are predicted, on physical metallurgy grounds, to lead to superior performance to EUROFER on low temperature and helium embrittlement [67]. This prediction also holds for ODS steels [eg.…”
Section: High Temperature Ferritic-martensitic Steelsmentioning
confidence: 99%
“…These steels are expected to exhibit low-temperature embrittlement problems, but, on the positive side, their high density of nano-scale precipitates and microstructures are predicted, on physical metallurgy grounds, to lead to superior performance to EUROFER on low temperature and helium embrittlement [67]. This prediction also holds for ODS steels [eg.…”
Section: High Temperature Ferritic-martensitic Steelsmentioning
confidence: 99%
“…A review by Zinkle et al has shown the development of materials with point defect sink strengths above ~10 16 m -2 can significantly suppress several of the radiation-induced processes seen in nuclear materials, such as radiation-induced hardening [3]. Such studies have shown the importance of the sink density to irradiation resistance, particularly when high dose applications are desired.…”
Section: Numerous Light Water Reactor (Lwr) Nuclear Power Plants In Tmentioning
confidence: 99%
“…Even though some classes of steels and other metal alloys are known to have high radiation tolerance, their properties do start to change immediately after the onset of irradiation [10,13]. This has motivated an intense ongoing search for new classes of materials with improved radiation hardness.…”
mentioning
confidence: 99%